A Study on State of Agriculture in India Before 1947 (International Journal of Food and Nutritional Sciences, 2022)
Agriculture is the backbone of the Indian economy. The geographical position of India has been very beneficial for agricultural activities. The physical factors found in India such as climate, soil, and relief were very helpful in the cultivation of so many crops. So from ancient times, the Indians had chosen agriculture as their primary means of livelihood. In the coming years it would be essential to increase food production in developing countries especially India. This however involves finding viable solutions to several of detailed technological, organizational and policy matters including market economies, study on seeds and inputs: agricultural extension, credit, rural infrastructure, storage connection to markets, rural nonfarm work opportunities and food price normalization. This article analyzes the state of agriculture in the past 100 years in India. Furthermore it debated the agricultural development and the part played by agricultural production in the development phase and the interrelations between agriculture and other sectors of the economy, the predictors of the Green revolution and explain the underpinnings of agricultural production growth in India, the regional development including the effect of green revolution in the economic development of the country